“And Geiseric levelled the walls of all the cities." On the uselessness of fortifications: a Vandal concept of defense? - (:unkn) unknown (My University, 2025)
Communication presented as part of a round table for Master and Doctorat students under the direction of Isabelle Pimouguet-Pedarros. This 7th edition of the round table on war violence, which Pimouguet-Pedarros has been directing for years, focuses on the subject of violence in the context of siege warfare, as it is titled, “Guerre de siège et violences de masse de l'Antiquité à nos jours (Siege warfare and mass violence from Antiquity to the present days).From 462 to 476, Geiseric, king of the Vandals, took care to level the walls of the cities under his control, with the exception of those of Carthage. The rapid fall of the Vandal kingdom in 533 is sometimes attributed to this alleged strategic error. Yet, fortified cities in Vandal Africa were not that absent. The idea that this decision was the result of political incompetence is itself a retrospective interpretation of the decision. During the Justinian Wars, it is assumed that the destruction in Africa was less palpable than that of Italy, and even this "small amount" of destruction is difficult to support by archaeology. The concept of “protection” also seems to have been absent from the Vandals' vision of “defense”, as portrayed by Procopius of Caesarea. This communication proposes some hypotheses that attempt to explain the Vandal dismantling enterprise, apart from alleged “poliorcetic incompetence”, all by connecting it to the appearant Vandal aversion to fortified cities in 533.
Keywords: African Research